2015
DOI: 10.1111/acel.12358
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and dietary restriction on the tissue‐specific metabolome of Drosophila

Abstract: Dietary restriction (DR) is a robust intervention that extends lifespan and slows the onset of age-related diseases in diverse organisms. While significant progress has been made in attempts to uncover the genetic mechanisms of DR, there are few studies on the effects of DR on the metabolome. In recent years, metabolomic profiling has emerged as a powerful technology to understand the molecular causes and consequences of natural aging and disease-associated phenotypes. Here, we use high-resolution mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 57 publications
6
89
0
4
Order By: Relevance
“…Colinet et al, 2012;Hoffmann et al, 2014;Laye et al, 2015;Williams et al, 2015). In this study, we found clear variation in metabolic profi le across larval, pupal and adult developmental stages, as well as sex differences in the overall profi le that appear to increase throughout development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colinet et al, 2012;Hoffmann et al, 2014;Laye et al, 2015;Williams et al, 2015). In this study, we found clear variation in metabolic profi le across larval, pupal and adult developmental stages, as well as sex differences in the overall profi le that appear to increase throughout development.…”
Section: Discussionmentioning
confidence: 99%
“…Colinet et al, 2012) but far fewer than some other research (e.g. Laye et al, 2015), which may refl ect our specifi c need to optimise the gas chromatography process for sample types from different holometabolous stages. Of these compounds, 14 were present in both sexes and all stages.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, studies in worms (Fuchs et al 2010), mice (Tomas-Loba et al 2013), and humans (Yu et al 2012) have documented changes in the metabolome during the aging process. Recently, untargeted metabolomics analysis in flies (Hoffman et al 2014) has suggested that DR might reverse age-dependent metabolic reprogramming at the tissue (Laye et al 2015) and whole-organism (Avanesov et al 2014) levels. Despite these studies, the mechanisms underlying age-dependent metabolic reprogramming, the nature of the metabolites that change with time, and their effect on life span are still poorly characterized.…”
mentioning
confidence: 99%
“…Tempoh berpuasa juga telah terbukti mempunyai kesan antimutagenik, antibakteria dan antikarsinogenik (Lee & Longo 2011). Kesan pengehadan kalori juga mempengaruhi metabolit di dalam tubuh terutama dalam metabolom hepar (Laye et al 2015;Jové et al 2014). Namun demikian, kebanyakan kajian dijalankan melibatkan spesies haiwan dan kurang kajian dijalankan ke atas manusia.…”
Section: Pendahuluanunclassified